Biochemical and Ultrastructural Studies for Toxicity of Kaempferol Derivative Recovered from the Plant Lysimachia Ramosa - Sarkar, Ashish; Roy, Bishnupada (Defence Life Science Journal, 2022)
Leaves of Lysimachia ramosa are used by various tribes of Meghalaya to cure intestinal helminth infections. Preliminary investigations disclosed impressive anthelmintic effects of the kaempferol derivative, an active component of the plant, however, toxic effects on its consumers, if any, are not known. Therefore, the present study has been undertaken to investigate the acute and sub-acute toxic effects of kaempferol derivative, of the plant, taking Wistar rats as a model. Following OECD 407, 250 mg, 500 mg, and 1000 mg/kg body weight doses of the active component have been selected to treat the animals for 28 days. On the 29th day, the animals have been sacrificed to assess different toxicological effects on animals. The LD50 value of the anthelmintic component was found to be more than 5000 mg/kg body weight of rats. Histological, ultrastructural, haematological, biochemical, and organo-somatic (HSI and RSI) studies demonstrate changes in surface characteristics of various cellular organelles of different vital organs such as the liver, kidney, and intestine. Alterations were also recorded in different vital enzymes such as AST, ALT, and ALP in the phytochemical exposed rats at higher doses. The results revealed that treatment with the active component at a higher concentration may lead to toxicological effects if treatment persists for a longer period.